A novel fusion protein containing the receptor binding domains of C. difficile toxin A and toxin B elicits protective immunity against lethal toxin and spore challenge in preclinical efficacy models - Tian, Jing-Hui; Fuhrmann, Steven R.; Kluepfel-Stahl, Stefanie; Carman, Robert J.; Ellingsworth, Larry; Flyer, David C. (Vaccine, 2012)
► C. difficile ToxinA:toxin B fusion protein. ► Induction of toxin neutralizing antibody. ► Immunoprotection against an in vivo C. difficile spore challenge. Antibodies targeting the Clostridium difficile toxin A and toxin B confer protective immunity to C. difficile associated disease in animal models and provided protection against recurrent C. difficile disease in human subjects. These antibodies are directed against the receptor binding domains (RBD) located in the carboxy-terminal portion of both toxins and inhibit binding of the toxins to their receptors. We have constructed a recombinant fusion protein containing portions of the RBD from both toxin A and toxin B and expressed it in Escherichia coli. The fusion protein induced high levels of serum antibodies to both toxins A and B capable of neutralizing toxin activity both in vitro and in vivo. In a hamster C. difficile infection model, immunization with the fusion protein reduced disease severity and conferred significant protection against a lethal dose of C. difficile spores. Our studies demonstrate the potential of the fusion protein as a vaccine that could provide protection from C. difficile disease in humans.